Language and Desire in Seneca's "Phaedra." - Segal, Charles, 1936-2002 (Princeton Legacy Library, 2017)
This close reading of Seneca's most influential tragedy explores the question of how poetic language produces the impression of an individual self, a full personality with a conscious and unconscious emotional life. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.